2012
DOI: 10.17221/284/2011-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage temperature on the quality of dry fermented sausage Poličan

Abstract: Kameník J., Saláková A., Bořilová G., Pavlík Z., Standarová E., Steinhauser L. (2012): Effect of storage temperature on the quality of dry fermented sausage Poličan. Czech J. Food Sci., 30: 293-301.The influence of different storage temperatures (5°C and 15°C) on the quality of vacuum-packed dry fermented sausage Poličan was determined. The salami mixture, finished salamis (the maturing period of 30 days), and salamis stored for 30, 60, 90, and 120 days were analysed. The analyses performed (physical/chemical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…During the storage, LAB at 4°C remained unchanged, while batches at 20°C decreased. Contrarily to our results, (Kameník et al., 2012) , showed that mesophilic and LAB were not affected by temperature of storage (5°C and 15°C) during 120 days in vacuum‐packaged dry‐fermented sausages. The counts of yeasts and molds were significantly increased during storage and they were significantly higher at 4°C than at 20°C at the end of storage.…”
Section: Resultssupporting
confidence: 85%
“…During the storage, LAB at 4°C remained unchanged, while batches at 20°C decreased. Contrarily to our results, (Kameník et al., 2012) , showed that mesophilic and LAB were not affected by temperature of storage (5°C and 15°C) during 120 days in vacuum‐packaged dry‐fermented sausages. The counts of yeasts and molds were significantly increased during storage and they were significantly higher at 4°C than at 20°C at the end of storage.…”
Section: Resultssupporting
confidence: 85%
“…The LAB population found in the tested products corresponds to this type of meat product (Garriga & Aymerich, 2007;Kameník et al, 2012b). Matagaras et al (2015) reported a LAB population of 8.0-9.0 log cfu/g in the Italian sausages Cacciatore (ripening period 20 days) and Felino (ripening period 40 days) prepared with a starter culture.…”
Section: Microbiological Analysismentioning
confidence: 83%
“…This compound also affects the taste of the final products in addition to the pH. Evaluation of the pH value and perhaps the lactic acid content as such is important from the viewpoint of evaluation of the course of the fermentation process and the quality of the sausages.In the products produced using traditional technology, the final pH value ranged from 4.4 to 4.7 and corresponds to products of the northern European type with rapid fermentation(Schwing & Neidhardt, 2007) Kameník, Sal akov a, Pavlík, Pospiech, and Steinhauserov a (2012b). found pH values from 4.6 to 5.3 in products at retail from four various producers that corresponded to product A trad Kameník et al (2013).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Sample 3 showed a considerably low pH value (4.32). In contrast, samples A-D had standard pH values that correspond to products of this type, such as Herkules or Poličan sausages (Kameník et al 2012a).…”
Section: Discussionmentioning
confidence: 96%